Model collaborative governance dalam pembangunan desa pada masa covid-19: studi di Kabupaten Lampung Selatan - Ardian Prabowo; Mujibur Rahman Khairul Muluk; Ainul Hayat (Universitas Merdeka Malang, 2021)
At present, the Covid-19 contagious disease outbreak can spread rapidly throughout the world, including Indonesia. Apart from having a negative impact on the health sector, it also impacts the economic, social, cultural, resilience, tourism and other sectors. This can threaten people in rural areas who have gaps in health accessibility and high levels of poverty compared to urban areas. So it is necessary to carry out village economic development, but still protect the health of rural communities from the Covid-19 disaster. This cannot be done by the government alone. Interdisciplinary and field cooperation is required by referring to the principles of collaborative governance. The research objective was to determine the ideal collaborative governance model in village development during the Covid-19 pandemic. This research uses qualitative methods with a descriptive approach. This method can be studied comprehensively and deeply. The results of this study indicate that in South Lampung Regency there are already several priority activities in the economic and health sectors, some of these priority activities such as Covid-19 Response Village, Village Cash Intensive Work, Village Fund Direct Cash Assistance (BLT), and other Infrastructure Development. These priority activities are collaborations carried out by the government, society and business